2008
DOI: 10.3748/wjg.14.1768
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and histopathological study on the duodenum of Strongyloides stercoralis hyperinfection

Abstract: AIM:To investigate endoscopic and histopathological findings in the duodenum of patients with Strongyloides stercoralis (S. stercoralis ) hyperinfection. METHODS:Over a period of 23 years , we investigated 25 patients with S. stercoralis hyperinfection who had had an esophagogastroduodenoscopy before undergoing treatment for strongyloidiasis. The clinical and endoscopic findings were analyzed retrospectively. R E S U LT S :Tw e n t y -f o u r ( 9 6 % ) o f t h e p a t i e n t s investigated were under immunoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 27 publications
2
88
1
2
Order By: Relevance
“…Kisimoto et al (5) also observed that 68% of 25 subjects studied had larvae of S. stercoralis in stool examination. Indeed, in 11 cases of HUPES, 80% of patients had stool sample examination positive for the agent found in biopsy, showing that intestinal parasitosis are a common neglected differential diagnosis.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Kisimoto et al (5) also observed that 68% of 25 subjects studied had larvae of S. stercoralis in stool examination. Indeed, in 11 cases of HUPES, 80% of patients had stool sample examination positive for the agent found in biopsy, showing that intestinal parasitosis are a common neglected differential diagnosis.…”
Section: Resultsmentioning
confidence: 92%
“…Kishimoto et al (5) , after investigation of 25 patients infected with S. stercoralis, also presented, as predominant symptoms, the presence of vomiting, diarrhea, weight loss and abdominal pain. Moreover, Kishimoto found the presence of sepsis in 12% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, se han descrito casos en que los hallazgos endoscópicos e histopatológicos no son métodos confiables para confirmar esta patología 9 . Los exámenes coproparasitológicos tienen poca sensibilidad en el diagnóstico de esta helmintiasis.…”
Section: Discussionunclassified